Selective Cell Penetrating Peptide‐Functionalized Polymersomes Mediate Efficient and Targeted Delivery of Methotrexate Disodium to Human Lung Cancer In Vivo. Issue 7 (27th December 2017) - Yang, Weijing; Xia, Yifeng; Fang, Yuan; Meng, Fenghua; Zhang, Jian; Cheng, Ru; Deng, Chao; Zhong, Zhiyuan
Abstract: It is a long challenge to develop nanomedicines that simultaneously possess tumor cell selectivity and penetration functions. Here, it is reported that selective cell penetrating peptide (RLWMRWYSPRTRAYGC)‐functionalized polymersomes (SCPP‐PS) mediate efficient and targeted delivery of methotrexate disodium (MTX) to human lung cancer in vivo. SCPP‐PS with an SCPP density of 18.7% is self‐crosslinked, has a small size (63–65 nm), and high MTX loading (up to 19.4 wt%), shows selective uptake and fast penetration into A549 lung cancer cells, and efficiently releases MTX intracellularly. Interestingly, MTX‐loaded SCPP‐PS (MTX‐SCPP‐PS) displays much lower IC50 than those of MTX‐PS and free MTX. Installing SCPP to polymersomes has no detrimental effect to their long blood circulation time but significantly increases drug accumulation in A549 tumor (5.3% injected dose per gram at 8 h post injection). Remarkably, SCPP‐PS exhibits deep penetration in to A549 tumors. MTX‐SCPP‐PS completely inhibits tumor progression and significantly improves survival rates in mice bearing A549 lung tumor xenografts as compared to MTX‐PS and free MTX groups (median survival time: 75 vs 45 and 38 d, respectively), without causing noticeable adverse effects. These results highlight that functionalization of nanomedicines with SCPP is a feasible strategy to achieve efficient and targeted tumor therapy. Abstract : Lung cancer selective cell penetrating peptide‐decorated and reversibly crosslinked chimaeric polymersomes enable highly efficient loading and targeted delivery of hydrophilic anticancer drug, methotrexate disodium, to A549 lung tumor xenografts in nude mice, resulting in effective tumor penetration and suppression and significantly improved survival rate in comparison with Trexall and nontargeted controls.